Dynamics of Export, Imports, and Monetary Variables on Manufacturing Industry Output in Indonesia - Anis Puspita Sari; Aminudin Ma’ruf (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2026)
This study aims to analyze the short-term and long-term relationships and influences between international trade and monetary variables on the performance of the manufacturing industry sector in Indonesia. Manufacturing output is proxied by the Industrial Production Index (IPI). The variables used in this study include exports, imports, BI Rate, inflation, exchange rate, and money supply. This research uses monthly time series data from 2010–2024 and applies the Vector Error Correction Model (VECM) to examine both short-term and long-term relationships among the variables. The Impulse Response Function (IRF) is used to analyze the dynamic response of manufacturing output to economic shocks, while Forecast Error Variance Decomposition (FEVD) is used to measure the contribution of each variable in explaining the variation in manufacturing output. The results show the existence of a long-run relationship between exports, imports, monetary variables, and manufacturing output in Indonesia. In the short run, most variables do not significantly affect manufacturing output, but the significant Error Correction Term (ECT) indicates an adjustment mechanism toward long-run equilibrium. In the long run, exports, BI Rate, and money supply have a positive and significant effect, while imports, inflation, and exchange rate have a negative and significant effect on manufacturing output. The IRF results indicate fluctuating responses in the early periods before gradually stabilizing, while FEVD shows that the contribution of exports, imports, and monetary variables in explaining manufacturing output increases in the long run.